Assessment of Osgood-Schlatter Disease and the Skeletal Maturation of the Distal Attachment of the Patellar Tendon in Preadolescent Males. Issue 7 (18th July 2014) - Yanagisawa, Shinya; Osawa, Takashi; Saito, Kenichi; Kobayashi, Tsutomu; Tajika, Tsuyoshi; Yamamoto, Atsushi; Iizuka, Haku; Takagishi, Kenji
Background: Osgood-Schlatter disease (OSD) is a traction apophysitis of the tibial tuberosity. Ultrasonography (US) is able to detect pathologic changes, such as cartilage swelling and fragmentation of the tibial tubercle ossification center. Purpose: To compare the US stages of tibial tuberosity development and the physical features and prevalence of OSD in this patient cohort. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Subjects included 238 males (n = 476 joints) with a mean age of 11.4 ± 1.6 years (range, 7-14 years). The tibial tuberosity development on US was divided into 3 stages: the cartilaginous stage (stage C), apophyseal stage (stage A), and epiphyseal stage (stage E). It was then investigated whether the subjects had pain in the tibial tuberosity on application of pressure. Age, height, body weight, body mass index (BMI), heel-buttock distance (HBD, cm), and straight-leg raise angle (SLRA) were evaluated. To confirm the diagnosis of OSD, the participant had to fulfill the following clinical criteria: pain with direct pressure on the tibial apophysis, fragmentation of the bone, and irregularity of the ossification center detected by US. Results: The tibial tuberosity was stage C in 195 knees, stage A in 105 knees, and stage E in 176 knees. The subjects' heights, weights, and BMIs significantly increased with advancing development of the tibial tuberosity. The HBD increased in stage E ( P < .01). The SLRA was not significantly different among groups. There was fragmentation of the bone and irregularity of the ossification center in 32 knees (6.8%): 0 in stage C, 21 (4.3%) in stage A, and 11 (2.3%) in stage E. Fragmentation of the bone and irregularity were observed significantly more often in stage A ( P < .01). On the other hand, there were 10 joints with OSD (2.1%): 0 in stage C, 3 (0.6%) in stage A, and 7 (1.5%) in stage E. OSD was observed significantly more often in stage E than in the other stages ( P < .05). Conclusion: The present study showed that the HBD increased from stage A to stage E. The prevalence of OSD was highest in stage E.